Analysis of Movement Skills of SD Alam Lubuklinggau Students After the Post Covid-19 Pandemic - Darmawan, Risky; Lian, Bukman; Junaidi, Ilham Arvan (Journal of Social Work and Science Education, 2023)
The purpose of this study was “to determine the Analysis of Movement Skills of Students of SD Alam Lubuklinggau After the Post Covid-19 Pandemic”. This is quantitative descriptive research by providing basic motion, so that the results of skills are obtained and analysis is carried out. The data analysis used in this study calculated the percentage of Movement Skills of SD Alam Lubuklinggau Students After the Post Covid-19 Pandemic. The result was found that the condition of students’ movement skills was still relatively poor after the COVID-19 pandemic. In addition, the phenomenon that occurs shows that children are more interested in doing electronic games -such as online games, gadgets and, other electronic games. Children feel very comfortable to do the game without feeling bored for a long period of time. On the other hand, the child himself stated that he only felt tired and bored with what was taught by the teacher and did not like to do running and jumping activities.